Cognitive-Enhancing Effect of a Hydroethanolic Extract of Crinum macowanii against Memory Impairment Induced by Aluminum Chloride in BALB/c Mice - Mohammed S. Jilani; Dexter Tagwireyi; Louis L. Gadaga; Charles C. Maponga; Cosmas Mutsimhu (Behavioural Neurology)
Crinum macowanii is a bulbous plant indigenous to many parts of Southern Africa. Extracts of C. macowanii have gained interest since the discovery of various alkaloids, few of which possess acetylcholinesterase inhibitory activity. The present study was performed to evaluate the effect of a crude hydroethanolic extract of C. macowanii against aluminum chloride-induced memory impairment in mice using the Morris water maze and the novel object recognition task. C. macowanii (10, 20, and 40 mg/kg p.o) was administered daily for five weeks, while donepezil (3 mg/kg p.o) was used as the positive control. C. macowanii at a dosage of 40 mg/kg showed a significantly lower escape latency than the negative control (P<0.0001) and was found to be comparable to donepezil 3 mg/kg in the Morris water maze test. C. macowanii at 40 mg/kg exhibited a significantly higher discrimination index than aluminum chloride-treated mice in the novel object recognition task. The results may support the usefulness of C. macowanii in the management of dementia and related illnesses.